The establishment and activity of bacterial inoculant immobilized in agar compared with those of alginate and perlite after being introduced into soil - Pongrawee Nimnoi (2018)
© 2017, Chiang Mai University. All rights reserved. The objectives of this study were to select effective bacteria that produced high amounts of IAA and ammonia, and to determine the potential of using agar compared with alginate and perlite as cell immobilization materials to maintain a long survival of the inoculant strains. The Ensifer spp. strains LP2/20, NK2/9 and Bacillus sp. strain NK2/17 were selected, immobilized and stored at 30 °C for 15 days. After 15 days of storage, Ensifer sp. strain LP2/20 immobilized in agar exhibited the highest number of bacterial survival which was significantly different from those of other materials. In pot experiments, the establishment and activity of the inoculant after 15 days of introducing into soil were investigated by PCR-denaturing gradient gel electrophoresis (DGGE) and Reverse Transcription (RT) PCR-DGGE. Cloning and sequencing of 16S rRNA gene fragments obtained from DNA- and RNA-based DGGE gels confirmed that agar and alginate were the preferable immobilization materials that prolonged the survival times and supported the establishment of the inoculant after being introduced into soil rather than absorption in perlite. The inoculant immobilized in agar and alginate were still metabolically active after 15 days of introducing into soil, while usage of perlite as a carrier and liquid inoculation were proved ineffective in maintaining the activity of the inoculant. Moreover, inoculation with either immobilization material exhibited the potential to change bacterial community structure in soil.